2015
DOI: 10.4314/wsa.v41i5.10
|View full text |Cite
|
Sign up to set email alerts
|

Passive remediation of acid mine drainage using cryptocrystalline magnesite: A batch experimental and geochemical modelling approach

Abstract: Acid mine drainage is generated when mining activities expose sulphidic rock to water and oxygen leading to generation of sulphuric acid effluents rich in Fe, Al, SO 4 and Mn with minor concentrations of Zn, Cu, Mg, Ca, Pb depending on the geology of the rock hosting the minerals. These effluents must be collected and treated before release into surface water bodies. Mining companies are in constant search for cheaper, effective and efficient mine water treatment technologies. This study assessed the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The morphology by SEM showed the presence of spherical structures. Masindi (2014) has reported that magnesite contains a fraction of crystalline phases and a portion of amorphous phase. The presence of Mg, C, O, Si, and Ca confirms that the material under study is magnesite.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The morphology by SEM showed the presence of spherical structures. Masindi (2014) has reported that magnesite contains a fraction of crystalline phases and a portion of amorphous phase. The presence of Mg, C, O, Si, and Ca confirms that the material under study is magnesite.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…The study conducted by Sparks (1997) pointed out that aluminum and iron oxides have high PZC values (usually at pH 8). The high PZC in bentonite clay is an attribute of the presence of aluminum and iron oxide or (Masindi 2014). The pH pzc value of a material is a reflection of the individual pH pzc values of the components present.…”
Section: Point Of Zero Charge (Pzc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of applying magnesite as an initial remediation step in an integrated AMD management system was evaluated for neutralization and metal attenuation using batch laboratory experiments and geochemical modeling (Masindi et al, 2015). It was found that magnesite had the potential to neutralize AMD, reduce sulfate, and precipitate metals.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Traditionally, the remediation of AMD has been carried out through a range of active and passive technologies. Active treatment technologies involve the use of alkaline reagents such as limestone and lime [21,22], and magnesite [23]. Some of the limitations of limestone treatment processes include armoring of limestone particles by amorphous ferric hydroxide precipitates which reduces the eiciency of treatment process and atains a maximum pH of 7 which leaves species such as Mg in solution [24].…”
Section: Acid Mine Drainage Treatment Using Coal Ly Ashmentioning
confidence: 99%